The Legal Status of Ghostwriters in Copyright Assignment Agreements: A Perspective on Moral Rights and Economic Rights (International Journal of Applied Research and Innovation, 2026)
This study examines the legal status of ghostwriters within copyright assignment agreements by analyzing the interaction between moral rights and economic rights under Indonesian copyright law. The research employs a non empirical legal method based on statutory interpretation, conceptual analysis, and doctrinal synthesis. Primary legal materials consist of Law Number 28 of 2014 concerning Copyright and representative ghostwriter contractual arrangements, while secondary materials include contemporary scholarship on authorship, copyright ownership, contractual transfer mechanisms, and moral rights theory. The analysis demonstrates that ghostwriters retain their legal position as original creators despite contractual concealment of their identities and the transfer of economic interests to clients. Copyright assignment agreements function primarily as instruments for transferring exploitation rights and commercial benefits rather than authorial status. The findings further reveal a persistent normative tension between freedom of contract and the inalienable nature of moral rights. Although clients may acquire extensive economic control over a work, rights of attribution and integrity remain legally connected to the ghostwriter. The study concludes that copyright law accommodates commercial transfer while preserving continuing legal protection for creators, thereby establishing a balanced framework between contractual autonomy and author centered copyright principles.